Autonomy and operational concept for self-removal of spacecraft: Status detection, removal triggering and passivation. (November 2019) - Wander, Alexandra; Konstantinidis, Konstantinos; Förstner, Roger; Voigt, Philipp
Abstract: The growing population of space debris is posing a threat to future spacecraft in Earth orbit. The technology for self-removal of spacecraft, TeSeR, is an innovative project of eleven European partners coordinated by Airbus Defense & Space within the HORIZON2020 framework of the European Commission with the goal to develop a removal module that can be carried into orbit by future spacecraft of any size and mass into any orbit, interconnected only by a standardized interface. At early 2019, a prototype shall already have demonstrated the main functions on ground. This paper introduces the mission and operational concept as well as the functional architecture and presents the autonomy considerations for the design of the overall post-mission disposal module focusing on three areas: the status detection of the host spacecraft by the developed post-mission disposal module, the removal triggering by the post-mission disposal module in case of lost link to ground station and malfunctioning host spacecraft as well as the passivation options of the host spacecraft and the post-mission disposal module itself. Highlights: Introducing the "Technology for Self-Removal of Spacecraft" project. Operational concepts for an independent post-mission disposal module. Functional architecture for a post-mission disposal module. Autonomous status detection and removal triggering for post-mission disposal. Complete listing of passivation techniques.